Increasing Micro, Small and Medium Enterprises to Strengthen Community Economic Resilience - Yeni, Afni; Nasrah, Rasidah; Dini, Suci Rahma (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the Development of Micro, Small and Medium Enterprises (SMEs) to Strengthen the Economic Resilience of the Community. In this study, the method used is descriptive qualitative. Data collection techniques used in this study are observation, interviews and documentation. The type of data used is primary data. The data analysis technique used in this study is a descriptive qualitative method. The informants in this study were ten (10) people, namely people who have Micro, Small and Medium Enterprises in Nagari Tanjung Bingkung. In business development, there are many ways that can be done by business actors in Nagari Tanjung Bingkung such as development through social media, development by being delivered to collectors, and there are also those delivered to shops and markets. Carrying out online promotions is a method that is widely used by business actors in Tanjung Bingkung. The results of this study indicate that in strengthening economic resilience, the people of Nagari Tanjung Bingkung have opened Micro, Small and Medium Enterprises (SMEs) with marketing that has reached various regions and traditional markets. Most of those who open Micro, Small and Medium Enterprises are housewives, because by doing so they can improve the family economy.